Knowledge, attitude, and practice of adolescent girls towards reducing malnutrition in Maiduguri Metropolitan Council, Borno State, Nigeria: cross-sectional study - Shapu, Ruth Charles; Ismail, Suriani; Ahmad, Norliza; Lim, Poh Ying; Njodi, Ibrahim Abubakar (Multidisciplinary Digital Publishing Institute, 2020)
Addressing the gap in knowledge, attitude, and practice among adolescent girls are important as malnutrition has a negative effect on their future generation. This study aimed to determine the knowledge, attitude, and practice of adolescent girls towards reducing malnutrition in Maiduguri Metropolitan Council, Borno State, Nigeria. This was a school-based cross-sectional study conducted among 612 adolescent girls (10 to 19 years old). KoBo collect toolbox was used for the data collection between 3 June and 31 July 2019. Multivariable logistic regression was used to identify predictors of knowledge, attitude, and practice towards reducing malnutrition. The majority of respondents (451, 80.2%; 322, 57.3%) had poor knowledge and attitude towards reducing malnutrition respectively, 278 (49.5%) had poor practice towards reducing malnutrition. Schooling (GGSS; p = 0.022; Shehu Garbai; p = 0.003) was a significant predictor of knowledge. Religion (p = 0.023), information (p < 0.001) and motivation (p < 0.001) were significant predictors of attitude. School (GGSS; p < 0.001; GGC; p < 0.001; Shehu garbai; p < 0.001; Bulabulin; p = 0.030; Zajeri day; p = 0.049), education of father (p = 0.001), information (p = 0.026) and behavioral skill (p = 0.019) were significant predictors of practice. There is a need to focus on both school-based and community-based health education intervention to address the poor knowledge, attitude, and practice among adolescent girls for a healthier future.